Horse - Clutton-Brock, Juliet; Young, Jerry; Shone, Karl (New York : Knopf, 1992)
A photo essay introducing members of the horse family, their evolution, behavior, importance, history, breeding, and training. Includes major international breeds of domestic horses.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
6.5
5-8
Keywords: Horses -- Juvenile literature; Equus -- Juvenile literature; Horse breeds -- Juvenile literature; Equidae; Horses; Horse breeds; Equidae; Horses